Perceptions of healthcare professionals and people with type 2 diabetes on emotional support: a qualitative study. Issue 1 (April 2020) - Hadjiconstantinou, Michelle; Dunkley, Alison J; Eborall, Helen; Robertson, Noelle; Khunti, Kamlesh; Davies, Melanie
No abstract available